Modulating retinoid-X-receptor alpha (RXRA) expression sensitizes chronic myeloid leukemia cells to imatinib in vitro and reduces disease burden in vivo - Rajamani, Bharathi M.; Illangeswaran, Raveen Stephen Stallon; Benjamin, Esther Sathya Bama; Balakrishnan, Balaji; Jebanesan, Daniel Zechariah Paul; Das, Saswati; Pai, Aswin Anand; Vidhyadharan, Rakhi Thalayattu; Mohan, Ajith; Karathedath, Sreeja; Abraham, Aby; Mathews, Vikram; et al. (Frontiers in Pharmacology, 2023)
Introduction: The ligand-activated transcription factors, nuclear hormone receptors (NHRs), remain unexplored in hematological malignancies except for retinoic acid receptor alpha (RARA). Methods: Here we profiled the expression of various NHRs and their coregulators in Chronic myeloid leukemia (CML) cell lines and identified a significant differential expression pattern between inherently imatinib mesylate (IM)-sensitive and resistant cell lines. Results: Retinoid-X-receptor alpha (RXRA) was downregulated in CML cell lines inherently resistant to IM and in primary CML CD34+ cells. Pre-treatment with clinically relevant RXRA ligands improved sensitivity to IM in-vitro in both CML cell lines and primary CML cells. This combination effectively reduced the viability and colony-forming capacity of CML CD34+ cells in-vitro. In-vivo, this combination reduced leukemic burden and prolonged survival. Overexpression (OE) of RXRA inhibited proliferation and improved sensitivity to IM in-vitro. In-vivo, RXRA OE cells showed reduced engraftment of cells in the bone marrow, improved sensitivity to IM, and prolonged survival. Both RXRA OE and ligand treatment markedly reduced BCR::ABL1 downstream kinase activation, activating apoptotic cascades and improving sensitivity to IM. Importantly, RXRA OE also led to the disruption of the oxidative capacity of these cells. Conclusion: Combining IM with clinically available RXRA ligands could form an alternative treatment strategy in CML patients with suboptimal response to IM.